2013
DOI: 10.1080/09712119.2013.824889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pistachio by-products in replacement of alfalfa hay on ruminal fermentation, blood metabolites, and milk fatty acid composition in Saanen dairy goats fed a diet containing fish oil

Abstract: (2014) Effects of pistachio by-products in replacement of alfalfa hay on ruminal fermentation, blood metabolites, and milk fatty acid composition in Saanen dairy goats fed a diet containing fish oil, Journal of Applied Animal Research, 42:2,[186][187][188][189][190][191][192][193] The objective of this study was to investigate the effects of pistachio by-products (PBP) in replacement of alfalfa hay (AH) on ruminal fermentation, blood metabolites, and milk fatty acid composition in Saanen dairy goats fed a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
3
15
3
1
Order By: Relevance
“…Similarly, no effect of feeding PBP diets (30% of diets DM) on lambs performances were reported during the finishing period (Norouzian and Ghiasi, 2012). In contrast to our result, Ghaffari et al (2014) showed that substitution of PBP for alfalfa hay (30% of diets DM) decreased dry matter intake of Saanen dairy goats.…”
Section: Animal Performancecontrasting
confidence: 86%
See 1 more Smart Citation
“…Similarly, no effect of feeding PBP diets (30% of diets DM) on lambs performances were reported during the finishing period (Norouzian and Ghiasi, 2012). In contrast to our result, Ghaffari et al (2014) showed that substitution of PBP for alfalfa hay (30% of diets DM) decreased dry matter intake of Saanen dairy goats.…”
Section: Animal Performancecontrasting
confidence: 86%
“…In the present study tannin reduction by treatments may reduce tannin-protein complex and consequently increase digestion of protein in the intestine of lambs. In contrast to these results, Ghaffari et al (2014) reported that replacement of PBP with and without PEG for alfalfa hay (30% of diets DM) had no effect on serum glucose, BUN, albumin, total protein, cholesterol and TG of Saanen goat.…”
Section: Blood Metabolitesmentioning
confidence: 55%
“…In the study of Forough and Fazaeli (2005), CP, NDF, ADF and ME values were determined as 9.2-12.0%, 30-36%, 21-28% and 7.1-7.5 MJ/kg DM, which were consistent with obtained values of this study. Condensed tannin content of pistachio PB in the present study (2.62%) was similar to the values (2.07-2.63%) reported by Boga et al (2013), but it was higher than the value (1.81%) reported by Ghaffari et al (2014). These differences can vary depending on variety of pistachio, geographic conditions, soluble sugar content of pistachio and harvest time (Bohluli et al 2007).…”
Section: Resultscontrasting
confidence: 37%
“…Similarly, some forages (e.g., Vicia sativa L., Lotus corniculatus L., Hedysarum coronarium L., and Lotus pedunculatus) can also contain a high number of polyphenols that affect the performance and metabolism of animals [103][104][105][106]. Relationship between total phenol content of by-products naturally rich in polyphenols (BPRP) (expressed in g/kg DM) and dry matter intake (DMI, expressed in kg/d) in sheep (♦) and goats ( ) (goats: [40,93,94,107]; sheep: [16,17,90,91]).…”
Section: Effect On Voluntary Feed Intakementioning
confidence: 99%